Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1126/sciadv.1500501
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically active biomimetic micropropellers for the penetration of mucin gels

Abstract: Magnetic microparticles decorated with enzymes can penetrate mucin, which is a barrier for most particle-based drug carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
249
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(262 citation statements)
references
References 62 publications
4
249
0
Order By: Relevance
“…Urea was also considered as fuel . In a recent example where urease was used as the engine, Patiño et al reported PS particle‐based micromotors with a rough amine‐functionalized SiO 2 shell urease conjugation .…”
Section: Fuel‐driven Nano/micromotorsmentioning
confidence: 99%
“…Urea was also considered as fuel . In a recent example where urease was used as the engine, Patiño et al reported PS particle‐based micromotors with a rough amine‐functionalized SiO 2 shell urease conjugation .…”
Section: Fuel‐driven Nano/micromotorsmentioning
confidence: 99%
“…We show that swimming occurs in a relatively large zone of Newtonian fluid, and that the assumptions within our approach are consistent with the result. We discuss whether recent artificial swimmers mimicking H. pylori's neutralization strategy [46] may be in the same swimming regime as the bacteria. Effect of local confinement by mucus on swimming.…”
mentioning
confidence: 99%
“…Recently, Walker et al [46] have fabricated artificial magnetic propellers with surface-bound urease to mimic the motility strategy of H. pylori through mucus. In our calculation, the main difference between the artificial propeller and the bacterium is that in the advection-diffusion model the propeller generates a constant flux instead of a constant concentration at its surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, such designs only concerned with the applications of cargo transport on the swimmer surface, which put significant limitations over the amount of the deliverable cargo, and hence the potential efficacy of the microrobotic operations (29,32,33).…”
Section: Design Fabrication and Mobility Of Microswimmersmentioning
confidence: 99%